(untitled) (African Journal of Biomedical Research, 2020)
Recent decline in stroke mortality engendered by improved treatment has led to an increase in post-stroke morbidity and related healthcare cost. Most of post-stroke morbidity is due to depression. Few studies have examined the association of contextual factors with post-stroke depression (PSD) using a multilevel framework. This study used multilevel modelling to examine both individual and contextual predictors of PSD in southwest, Nigeria. The study used secondary data from a comparative cross-sectional study of one hundred and thirty (130) stroke survivors. Participants were consenting adult (aged ≥18 years) residing in southwest Nigeria who have survived stroke in the last 3 to 24 months preceding the time of the study. Data were preliminarily analyzed using descriptive statistics including percentages and frequency tables. Bivariate association tests were carried out using Chi-square test. Multivariate analyses were performed using multilevel logit modeling and results were presented as odds ratio and their 95% Confidence Intervals (95% CI). All analyses were performed at 5% significance level. The mean (±standard deviation) age of participants was 59.54 ± 11.08 and most participants (53.6%) were female. Exactly half of the participants were retirees while most of them were currently married (82.3%), resided in urban (76.7%), and never used alcohol (73.8%). Prevalence of PSD in this study was 41.5%. Post-stroke depression was more likely among younger stroke survivors (OR=1.47; 95% CI: 1.16, 1.85), female (OR=1.37; 95% CI: 1.16, 1.60), alcohol users (OR=1.21; 95% CI: 1.04, 1.47), and the retired (OR=1.23; 95% CI: 1.04, 1.45). PSD was significantly associated with history of stressful life events and all depressed stroke survivors had considered suicide. Post stroke depression was common in younger survivors. Female survivors and alcohol users were more depressed. History of stressful life event is predictive of post stroke depression in this sample. Interventions focusing on women, alcohol users and people with history of stressful life events that had survived a stroke may reduce the burden of post stroke depression and possibilities of suicide